2020
DOI: 10.1186/s12933-020-01102-8
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin modifies the relationship between inflammation and arterial stiffness in hypertensive patients with different glucose tolerance

Abstract: Background: Ferritin, a crucial element for iron homeostasis, is associated with chronic diseases characterized by subclinical inflammation such as essential arterial hypertension and type 2 diabetes mellitus (T2DM), showing a prognostic value in different clinical settings. We investigated whether ferritin is associated with arterial stiffness (AS), an early indicator of atherosclerosis, and if it could act as effect modifier on the relationship between inflammation and AS in hypertensive patients with differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
14
1
Order By: Relevance
“…As shown in a study performed by Gong et al, AS became significant with increasing numbers of the metabolic components [ 101 ]. However, multiple regression analysis revealed that not only are MS components responsible for PWV level, but also age, sex, HR, serum uric acid level, and ferritin level were shown to significantly affect the relationship between inflammation and PWV [ 86 , 121 , 122 , 123 ]. Therefore, more studies are required to improve the interpretation of PWV in the treatment of MS patients.…”
Section: Importance Of Analyzed Research In Routine Clinical Practicementioning
confidence: 99%
“…As shown in a study performed by Gong et al, AS became significant with increasing numbers of the metabolic components [ 101 ]. However, multiple regression analysis revealed that not only are MS components responsible for PWV level, but also age, sex, HR, serum uric acid level, and ferritin level were shown to significantly affect the relationship between inflammation and PWV [ 86 , 121 , 122 , 123 ]. Therefore, more studies are required to improve the interpretation of PWV in the treatment of MS patients.…”
Section: Importance Of Analyzed Research In Routine Clinical Practicementioning
confidence: 99%
“…RDN also reduced whole-body norepinephrine spillover [ 49 ], did not significantly change plasma catecholamines [ 46 ], and had a mixed influence on aldosterone [ 45 , 47 , 48 , 50 ]. In addition, arterial stiffness is a leading biomarker of risk in hypertension [ 51 ], and ferritin represents an independent risk factor of arterial stiffness [ 52 ]. However, the close relationship between ferritin and RH still needs further study.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Diabetic macroangiopathy, a specific form of atherosclerosis secondary to diabetes, causes cerebro-cardiovascular diseases, which are correlated with high mortality and morbidity in diabetic patients. Previous studies have shown that subclinical inflammation and insulin resistance play significant roles in the development of atherosclerosis and diabetes mellitus (DM) [ 1 , 2 ]. In addition, the role of adipocytokines in the pathological physiology of diabetic macroangiopathy has attracted considerable attention of the scientific community in recent years.…”
Section: Introductionmentioning
confidence: 99%